Phosphate solubilizing activities of Actinomycetes isolated from Waigeo, Raja Ampat islands, West Papua - SRI WIDAWATI; ARIF NURKANTO; I MADE SUDIANA (Biodiversitas Journal of Biological Diversity, 2008)
Actinomycetes is a major microbial group observed in soil, and contributes to nutrient cycling. This study is intended to verify physiologicalcharacters and phosphate solubilizing ability of Actinomycetes isolated from soil of Raja Ampat, West Papua. Most of isolates (RCW16-9,RCW16-8, W5-6, RCW25-1, RCW26-5, W28-4, W3-1, W3-7, W17-7, and W10-1) belonged to Streptomyces genera. The isolates produceclear zone in Pivoskaya after 3 days incubation. The liquid growth of this isolate rapidly utilizes glucose, and after 24 days of incubationalmost 95% glucose was consumed. Decrease of pH from 6.1 to 4.3 may stimulate dissolution of calcium phosphate, and about 21 mg/L-Pwas observed in bulk solution. An increase of phosphomonoesterase activity during incubation is concomitant with the release oforthophosphate into bulk solution. Acidity of cultures increased may stimulate solubilization of calcium phosphate. Most strains producephosphomonoesterase enzyme, indicating that actinomycetes are important soil microbes responsible for mediation and stimulation of bothinorganic and organic phosphate dissolution. Physiological and biomass growth character of phosphate solubilizing actinomycetes could beimportant taxonomic indicator for identifying and grouping soil actinomycetes.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Actinomycetes, phosphate solubilizer, phosphomonoesterase, glucose